Potassium lithium niobate tantalate energy storage ceramic as well as preparation method and application thereof

By doping Bi and Li elements into the potassium tantalum niobate matrix, the breakdown field strength and energy storage efficiency of potassium bismuth tantalum niobate lithium energy storage ceramics are improved, which solves the problem of energy storage density and efficiency of existing lead-free dielectric ceramic capacitors. Low problem, achieving efficient energy storage density and efficiency.

CN119350024AActive Publication Date: 2025-01-24GUILIN UNIV OF ELECTRONIC TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411487645.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The existing lead-free dielectric ceramic capacitors have low energy storage density and energy storage efficiency, making it difficult to widely use in high-power energy storage devices.

Method used

By adding Bi5+ (Bi3+) and Li+ elements to the potassium tantalate niobate matrix, solid solution replacement and ion doping methods are used to improve the breakdown field strength, saturation polarization strength and energy storage efficiency of the material.

Benefits of technology

High energy storage density and high energy storage efficiency are achieved. Specifically, under a low electric field of 220kV/cm, the energy storage density reaches 1.75J/cm3 and the energy storage efficiency reaches 83.6%, which significantly improves the energy storage performance of ceramics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005099555730000071
    Figure BDA0005099555730000071
  • Figure HDA0005099555830000011
    Figure HDA0005099555830000011
  • Figure HDA0005099555830000021
    Figure HDA0005099555830000021
Patent Text Reader

Abstract

The invention discloses a potassium lithium niobate tantalate energy storage ceramic as well as a preparation method and application thereof, and belongs to the field of energy storage ceramics, the chemical composition general formula of the ceramic is (K1-xLix) [(Ta0. 63Nb0.37) 1-xBix] O3, and x is more than 0 and less than or equal to 0.01. By adding Bi < 5 + > (Bi < 3 + >) and Li < + >, relatively high energy storage density and energy storage efficiency are obtained. By means of solid solution replacement and ion doping, large saturation polarization intensity and small remanent polarization intensity can be obtained while the breakdown field intensity is improved, and therefore the energy storage performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage ceramics, and in particular to a potassium lithium tantalate niobate bismuth energy storage ceramic and a preparation method and application thereof. Background Art

[0002] With the continuous growth of the global population, the demand for fossil energy resources is increasing, the global environmental and climate crisis is becoming more and more serious, and energy shortage will be the main problem that needs to be faced in the future. Therefore, energy storage will be an important part of future development. At present, solid fuel cells are widely used in real life because they have the highest energy density, but they cannot meet the requirements of working under high voltage (hundreds to thousands of volts) due to their slow charge carrier migration speed. Compared with them, dielectric ceramic capacitors have higher power density and faster charge and discharge rates. These characteristics make dielectric ceramic capacitors have greater development prospects. At present, lead-based dielectric ceramic capacitors are still the mainstream in the market, but because they pollute the environment and cause potential damage to human health, it is more important to develop lead-free dielectric ceramic capacitors. At present, research on lead-free dielectric ceramic capacitors mainly focuses on BaTiO 3 (BT), Na 0.5 Bi 0.5 TiO 3 (NBT), BiFeO 3 (BF) and K 0.5 Na 0.5 NbO 3 (KNN) and other systems. However, the energy storage density and energy storage efficiency of these lead-free ceramic capacitors are relatively low, making them unable to be widely used in high-power energy storage devices. Therefore, it is more important to research and develop new lead-free dielectric ceramic capacitors with high energy storage density and high energy storage efficiency.

[0003] Generally speaking, in order to achieve high energy storage density, the material needs to have a large saturation polarization intensity, a high breakdown strength, and a low residual polarization intensity. These characteristics work together to effectively improve the energy storage efficiency of the material.

[0004] Different substrates, some of which may have energy storage properties, while others may show piezoelectricity and ferroelectricity. These substrates often have high polarization strength and high residual polarization strength. It is difficult to convert such substrates into energy storage materials by ordinary doping, such as KNN (potassium sodium niobate), PZT (lead zirconate titanate), AgNbO3, etc. Lead in these substrates pollutes the environment, and although KNN has the tendency to replace PZT, it is also a great challenge to regulate it so that it has excellent energy storage performance (currently, energy storage properties are often achieved by introducing a large number of other elements, which is relatively complicated). And some substrates may be difficult to achieve excellent energy storage performance no matter how they are regulated.

[0005] Potassium tantalate niobate is a typical lead-free ferroelectric material. However, it has a large residual polarization strength at room temperature and a low breakdown field strength. Therefore, it has not shown good properties in energy storage. Summary of the invention

[0006] Purpose of the Invention

[0007] In order to overcome the above-mentioned shortcomings, the purpose of the present invention is to provide a lithium potassium tantalate bismuth niobate energy storage ceramic and its preparation method and application. 5+ (Bi 3+ )、Li + The present invention can obtain a higher energy storage density and energy storage efficiency by means of solid solution replacement and ion doping, while improving its breakdown field strength, obtaining a larger saturation polarization intensity and a smaller residual polarization intensity, thereby improving its energy storage performance.

[0008] Solution

[0009] To achieve the purpose of the present invention, the technical solution adopted by the present invention is as follows:

[0010] In the first aspect, the present invention provides a lithium potassium tantalate niobate bismuth energy storage ceramic, the chemical composition of which is as follows: 1- x Li x )[(Ta 0.63 Nb 0.37 ) 1-x Bi x ]O 3 , where 0<x≤0.01.

[0011] Further, 0.001≤x≤0.01, optionally 0.003≤x≤0.01, optionally 0.003≤x≤0.009, optionally 0.003≤x≤0.007, optionally 0.003≤x≤0.005.

[0012] Furthermore, it is obtained by adding bismuth and lithium elements into a potassium tantalate niobate matrix.

[0013] Further, the following steps are included: press (K 1-x Li x )[(Ta 0.63 Nb 0.37 ) 1-x Bi x ]O 3 The molar ratio formula will be K 2 CO 3 , Li 2 CO 3 , Nb 2 O 5 、Bi 2 O 3 and Ta 2 O 5 The powders are mixed, ball-milled for the first time, pre-fired, ball-milled again, granulated, formed, debinded and sintered to obtain potassium lithium tantalate niobate bismuth energy storage ceramics.

[0014] Furthermore, the first ball milling and / or the second ball milling are both wet ball milling; optionally, a volatile solvent is used as the medium for ball milling, and the volatile solvent is anhydrous ethanol. The ball milling time can be 21 to 24 hours; and zirconium oxide balls can be used for ball milling.

[0015] Furthermore, the pre-firing temperature is 750-800°C, and the pre-firing time is optionally 6-10 hours, and the atmosphere is optionally oxygen-free; optionally air-free; optionally, the material after the first ball milling is heated to the pre-firing temperature at a heating rate of 1-5°C / min, and the heating rate is optionally 2°C / min.

[0016] Further, the granulation includes: adding a binder to the ball-milled material again to granulate;

[0017] Optionally, the amount of binder added is 3-5wt%, optionally 4wt%;

[0018] Optionally, the binder is polyvinyl alcohol;

[0019] Optionally, before adding the binder, the ball-milled material is sieved through a 80-120 mesh sieve, optionally a 100 mesh sieve.

[0020] Furthermore, the forming comprises: dry pressing the granulated particles obtained above at 100 MPa to obtain an embryo body.

[0021] Furthermore, the embryo is a disc with a diameter of 10 mm and a thickness of 1.4 mm.

[0022] Further, the debinding includes heat preservation at 500-600°C, and the debinding heat preservation time is optionally 80-120 minutes;

[0023] Optionally, during the debinding process, the rate of heating to the insulation temperature is 1-5°C / min, and optionally 2°C / min.

[0024] Further, the sintering includes maintaining the temperature at 1170-1200°C.

[0025] Optionally, the sintering holding time is 2-21 hours, optionally 10 to 21 hours, optionally 10 to 15 hours, and optionally 12 to 15 hours.

[0026] Optionally, during sintering, the rate of heating to the holding temperature is 0.5-5°C / min, and optionally 1-5°C / min.

[0027] In a third aspect, there is provided an application of the potassium lithium tantalate niobate bismuth energy storage ceramic described in the first aspect or the potassium lithium tantalate niobate bismuth energy storage ceramic prepared by the preparation method described in the second aspect in the preparation of capacitors.

[0028] Beneficial Effects

[0029] (1) The formula of the present invention does not contain the toxic element Pb, and is an environmentally friendly material. The potassium lithium tantalate niobate bismuth lead-free energy storage ceramic of the present invention has high energy storage density and energy storage efficiency.

[0030] (2) The preparation method of the potassium lithium tantalate niobate bismuth lead-free energy storage ceramic material of the present invention is simple, has good repeatability and good energy storage performance. For example, when the general formula is (K 0.995 Li 0.005 )[Ta 0.628 Nb 0.369 Bi 0.005 ]O 3 When the external electric field strength is 220 kV / cm at 25°C ambient temperature and 10 Hz test frequency, the energy storage density W rec 1.75 J / cm 3 The energy storage efficiency η is 83.6%, and its energy storage efficiency is excellent among all types of energy storage ceramics reported so far.

[0031] (3) The present invention dopes Bi and Li into (K 1-x )[(Ta 0.63 Nb 0.37 ) 1-x ]O 3 A new energy storage ceramic is obtained in the matrix material. The present invention greatly improves the breakdown field strength and energy storage density, refines the hysteresis loop, and greatly improves the energy storage efficiency of the ceramic.

[0032] (4) The sample composition of the present invention is simple, and only Bi and Li need to be doped into the matrix element. The preparation is simple, and the pre-firing temperature is low, which saves costs to a certain extent and speeds up the production cycle. The sintering temperature of the sample is below 1200°C, and the sample can achieve high energy storage efficiency and energy storage density under a low electric field of 220kv / cm. Energy storage ceramics with high energy storage density and efficiency under a low electric field will be safer in application, and the energy consumption will also be lower. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] One or more embodiments are exemplarily described by the pictures in the accompanying drawings, and these exemplary descriptions do not constitute limitations on the embodiments. The special word "exemplary" here means "used as an example, embodiment or illustrative". Any embodiment described as "exemplary" here is not necessarily interpreted as being superior or better than other embodiments.

[0034] Figure 1 This is a hysteresis loop diagram of the potassium lithium tantalate niobate bismuth ceramic material prepared in Examples 1 to 5 of Test Example 1 of the present invention.

[0035] Among them, 0 represents Example 1, 0.003 represents Example 2, 0.005 represents Example 3, 0.007 represents Example 4, and 0.009 represents Example 5.

[0036] Figure 2 According to the test example 1 of the present invention Figure 1 The parameter values ​​(energy storage density and energy storage efficiency) are calculated, where the horizontal axis represents the value of x, where 0 corresponds to Example 1, 0.003 corresponds to Example 2, 0.005 corresponds to Example 3, 0.007 corresponds to Example 4, and 0.009 corresponds to Example 5. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] In addition, in order to better illustrate the present invention, numerous specific details are provided in the specific embodiments below. It should be understood by those skilled in the art that the present invention can also be implemented without certain specific details. In some embodiments, raw materials, elements, methods, means, etc. well known to those skilled in the art are not described in detail, so as to highlight the main purpose of the present invention.

[0039] Unless explicitly stated otherwise, throughout the specification and claims, the term “comprise” or variations such as “include” or “comprising”, etc., will be understood to include the stated elements or components but not to exclude other elements or components.

[0040] The raw materials used in the present invention are all commercially available.

[0041] The present invention relates to a lead-free energy storage ceramic material of potassium lithium tantalate niobate bismuth. 1-x Li x )[(Ta 0.63 Nb 0.37 ) 1-x Bi x ]O 3 (where 0<x≤0.01) Calculate and weigh the mass of each powder. The preparation method adopts solid phase sintering method. The specific steps are:

[0042] (1) According to the formula, weigh the dry, high-purity powder raw materials, whose chemical formula and purity are: K 2 CO 3 (99.0%), Li 2 CO 3 (98.0%), Nb 2 O 5 (99.5%), Bi 2 O 3 (99.0%) and Ta 2 O 5 (99.5%).

[0043] (2) The powder raw materials, zirconium oxide balls and anhydrous ethanol ball milling media weighed in step 1 are placed in a nylon jar and ball milled in a ball mill for 21-24 hours. Subsequently, the uniformly mixed powder is pre-sintered in a muffle furnace. The heating and cooling rates of the muffle furnace are both 2°C / min, the pre-sintering temperature is 750-800°C, and the holding time is 6-10 hours to obtain (K 1-x Li x )[(Ta 0.63 Nb 0.37 ) 1-x Bi x ]O 3 The powder after pre-sintering synthesis.

[0044] (3) The powder obtained in step 2 is subjected to a second ball milling using anhydrous ethanol and zirconium oxide balls as the medium, and the ball milling time is 21-24 hours.

[0045] (4) The powder obtained in step 3 is dried and passed through a 100-mesh sieve, and a polyvinyl alcohol solution is added at a concentration of 4wt% based on 3-5wt% of the powder to prepare granules.

[0046] (5) The powder granulated in step 4 was dry-pressed at a pressure of 100 MPa to obtain a disc embryo with a diameter of 10 mm and a thickness of 1.4 mm.

[0047] (6) The embryo obtained in step 5 is kept at 500-600°C for 80-120 min for debinding, with a heating rate of 2°C / min.

[0048] (7) The debinding embryo obtained in step 6 is further heated at a rate of 2°C / min and kept at 1170-1200°C for 2-21 hours. After sintering, the embryo is cooled to room temperature and taken out.

[0049] (8) The sintered energy storage ceramic material sample obtained in step 7 is polished to a thickness of 0.2-0.4 mm, then ultrasonically cleaned and dried, and silver electrodes are coated on both sides for energy storage performance testing.

[0050] The hysteresis loops involved in the present invention are all measured by TF ANALYZER 2000HS ferroelectric comprehensive analyzer (aixACCTSystems GmbH, Germany), and the energy storage density and energy storage efficiency data are all calculated from the corresponding hysteresis loops.

[0051] Example 1

[0052] According to the general formula (K 1-x Li x )[(Ta 0.63 Nb 0.37 ) 1-x Bi x ]O 3 , where x=0, the molar ratio is calculated and the dry high-purity powder raw material is weighed; the weighed powder raw material is loaded into a nylon jar with zirconium oxide balls and anhydrous ethanol as ball milling media, and ball milled in a ball mill for 24 hours. Then the mixed powder is pre-sintered in a muffle furnace, the heating and cooling rate of the muffle furnace is 2℃ / min, the pre-sintering temperature is 750℃, and the temperature is kept for 10 hours to obtain K[Ta 0.628 Nb 0.369 ]O 3 The pre-sintered ceramic powder was ball-milled again for 24 hours, and the powder after the second ball-milling was dried and passed through a 100-mesh sieve. The sieved powder was added with 4% PVA (polyvinyl alcohol) for granulation. The obtained granulated particles were dry-pressed under a pressure of 100 MPa to obtain a disc embryo with a diameter of 10 mm and a thickness of 1.4 mm. The molded embryo was heated to 600°C for 2 hours to remove binder, and then heated to 1178°C for 12 hours, and then cooled to room temperature with the furnace. The sintering was completed, and K[Ta 0.628 Nb 0.369 ]O 3 Energy storage ceramics.

[0053] Example 2

[0054] According to the general formula (K 1-x Li x )[(Ta 0.63 Nb 0.37 ) 1-x Bi x ]O 3, The molar ratio of x=0.003 was calculated and the dry high-purity powder raw material was weighed; the weighed powder raw material was loaded into a nylon jar with zirconium oxide balls and anhydrous ethanol as ball milling media, and ball milled in a ball mill for 24 hours. Then the mixed powder was pre-sintered in a muffle furnace, the heating and cooling rate of the muffle furnace was 2℃ / min, the pre-sintering temperature was 750℃, and the temperature was kept for 10 hours to obtain (K 0.997 Li 0.003 )[Ta 0.628 Nb 0.369 Bi 0.003 ]O 3 The pre-sintered ceramic powder was ball-milled again for 24 hours, and the powder after the second ball-milling was dried and passed through a 100-mesh sieve. The sieved powder was granulated by adding 4% PVA (polyvinyl alcohol). The granulated particles were dry-pressed under a pressure of 100 MPa to obtain a disc embryo with a diameter of 10 mm and a thickness of 1.4 mm. The molded embryo was heated to 600°C for 2 hours to remove binder, and then heated to 1178°C for 12 hours, and then cooled to room temperature with the furnace. The sintering was completed, and (K 0.997 Li 0.003 )[Ta 0.628 Nb 0.369 Bi 0.003 ]O 3 Energy storage ceramics.

[0055] Example 3

[0056] According to the general formula (K 1-x Li x )[(Ta 0.63 Nb 0.37 ) 1-x Bi x ]O 3, The molar ratio of x=0.005 was calculated and the dry high-purity powder raw material was weighed; the weighed powder raw material was loaded into a nylon jar with zirconium oxide balls and anhydrous ethanol as ball milling media, and ball milled in a ball mill for 24 hours. Then the mixed powder was pre-sintered in a muffle furnace, the heating and cooling rate of the muffle furnace was 2℃ / min, the pre-sintering temperature was 750℃, and the temperature was kept for 10 hours to obtain (K 0.995 Li 0.005 )[Ta 0.628 Nb0.369 Bi 0.005 ]O 3 The pre-sintered ceramic powder was ball-milled again for 24 hours, and the powder after the second ball-milling was dried and passed through a 100-mesh sieve. The sieved powder was granulated by adding 4% PVA (polyvinyl alcohol). The granulated particles were dry-pressed under a pressure of 100 MPa to obtain a disc embryo with a diameter of 10 mm and a thickness of 1.4 mm. The molded embryo was heated to 600°C for 2 hours to remove binder, and then heated to 1178°C for 12 hours, and then cooled to room temperature with the furnace. The sintering was completed, and (K 0.995 Li 0.005 )[Ta 0.628 Nb 0.369 Bi 0.005 ]O 3 Energy storage ceramics.

[0057] Example 4

[0058] According to the general formula (K 1-x Li x )[(Ta 0.63 Nb 0.37 ) 1-x Bi x ]O 3, The molar ratio of x=0.007 was calculated and the dry high-purity powder raw material was weighed; the weighed powder raw material was loaded into a nylon jar with zirconium oxide balls and anhydrous ethanol as ball milling media, and ball milled in a ball mill for 24 hours. Then the mixed powder was pre-sintered in a muffle furnace, the heating and cooling rate of the muffle furnace was 2℃ / min, the pre-sintering temperature was 750℃, and the temperature was kept for 10 hours to obtain (K 0.993 Li 0.007 )[Ta 0.628 Nb 0.369 Bi 0.007 ]O 3 The pre-sintered ceramic powder was ball-milled again for 24 hours, and the powder after the second ball-milling was dried and passed through a 100-mesh sieve. The sieved powder was granulated by adding 4% PVA (polyvinyl alcohol). The granulated particles were dry-pressed under a pressure of 100 MPa to obtain a disc embryo with a diameter of 10 mm and a thickness of 1.4 mm. The molded embryo was heated to 600°C for 2 hours to remove binder, and then heated to 1178°C for 12 hours, and then cooled to room temperature with the furnace. The sintering was completed, and (K 0.993 Li 0.007 )[Ta 0.628 Nb 0.369 Bi 0.007 ]O 3 Energy storage ceramics.

[0059] Example 5

[0060] According to the general formula (K 1-x Li x )[(Ta 0.63 Nb 0.37 ) 1-x Bi x ]O 3, The molar ratio of x=0.009 was calculated and the dry high-purity powder raw material was weighed; the weighed powder raw material was loaded into a nylon jar with zirconium oxide balls and anhydrous ethanol as ball milling media, and ball milled in a ball mill for 24 hours. Then the mixed powder was pre-sintered in a muffle furnace, the heating and cooling rate of the muffle furnace was 2℃ / min, the pre-sintering temperature was 750℃, and the temperature was kept for 10 hours to obtain (K 0.991 Li 0.009 )[Ta 0.628 Nb 0.369 Bi 0.009 ]O 3 The pre-sintered ceramic powder was ball-milled again for 24 hours, and the powder after the second ball-milling was dried and passed through a 100-mesh sieve. The sieved powder was granulated by adding 4% PVA (polyvinyl alcohol). The granulated particles were dry-pressed under a pressure of 100 MPa to obtain a disc embryo with a diameter of 10 mm and a thickness of 1.4 mm. The molded embryo was heated to 600°C for 2 hours to remove binder, and then heated to 1178°C for 12 hours, and then cooled to room temperature with the furnace. The sintering was completed, and (K 0.991 Li 0.009 )[Ta 0.628 Nb 0.369 Bi 0.009 ]O 3 Energy storage ceramics.

[0061] Test Example 1

[0062] The ceramic bodies prepared in the above Examples 1 to 5 were respectively ground to a 0.1 mm thick slice using 400 mesh corundum; after ultrasonic cleaning and drying, high-temperature conductive silver paste was coated on both sides, placed in a muffle furnace at 600°C for 30 min for silver calcination, cooled naturally to room temperature, and analyzed using a ferroelectric analysis system TF ANALYZER

[0063] 2000HS (aixACCT Systems GmbH, Germany) measured the polarization intensity of ceramic materials at 25°C ambient temperature and 10Hz test frequency. The results are shown in Figure 1 , the detection and system calculation results of energy storage density and energy storage efficiency are as follows Figure 2 .

[0064] Figure 1The results show that with the increase of Bi and Li doping amounts, the hysteresis loop gradually becomes "thinner" and the residual polarization intensity decreases significantly.

[0065] Figure 2 The results show that compared with Example 1 (x = 0), after adding Bi and Li elements, the breakdown field strength E b The energy storage density and energy storage efficiency of the energy storage materials of Examples 1 to 5 are shown in Table 1. When x = 0 (Example 1), at an ambient temperature of 25°C and a test frequency of 10 Hz, when the applied electric field strength is 130 kV / cm (see Figure 1 ), the energy storage density W rec =0.55J / cm 3 , energy storage efficiency η = 34.8%, and the maximum electric field can only be loaded to 130kv / cm (burst strength). When x = 0.005 (Example 3), at 25°C ambient temperature and 10Hz test frequency, when the applied electric field strength is 220kV / cm, the energy storage density W rec =1.75J / cm 3 , energy storage efficiency η = 83.6%.

[0066] The properties of the energy storage materials prepared in Examples 1 to 5 are shown in Table 1.

[0067] Table 1. Performance of energy storage materials of Examples 1 to 5

[0068]

[0069] According to Table 1, after the addition of Bi and Li elements, the polarization strength of the ceramic material decreases slightly, the residual polarization strength decreases significantly, and the breakdown field strength increases significantly, thereby obtaining a high energy storage density and a high energy storage efficiency.

[0070] Generally speaking, energy storage density and efficiency gradually increase with the loading of the electric field, and Example 3 can obtain high energy storage performance under a low electric field of 220 kv / cm, indicating that the energy storage ceramics prepared by the present invention will be safer in application and have lower energy consumption.

[0071] The preparation method of the potassium lithium tantalate niobate bismuth lead-free energy storage ceramic material of the present invention is simple, has good repeatability and good energy storage performance. For example, when the general formula is (K 0.995 Li 0.005 )[Ta 0.628 Nb 0.369 Bi 0.005 ]O 3 (Example 3), at an ambient temperature of 25°C and a test frequency of 10 Hz, when the applied electric field strength is 220 kV / cm, its energy storage density W rec1.75 J / cm 3 The energy storage efficiency η is 83.6%. It has excellent energy storage efficiency, is safer to use, and consumes less energy.

[0072] Through continuous attempts and improvements, the inventors have been able to transform the KTN matrix into a new type of lead-free energy storage material, which is expected to expand the research system of energy storage materials. Moreover, only two elements need to be doped to achieve the improvement of its energy storage performance, which is simple and efficient. Currently, no one has reported on the potassium tantalate niobate matrix or even studied its energy storage performance. The present invention has opened up a new direction for energy storage materials.

[0073] In summary, the present invention has discovered a new energy storage ceramic (K 1-x )[(Ta 0.63 Nb 0.37 ) 1-x ]O 3 In the present invention, Bi and Li are doped into (K 1-x )[(Ta 0.63 Nb 0.37 ) 1-x ]O 3 The breakdown field strength and energy storage density are greatly improved in the matrix material, and the hysteresis loop is refined, and the energy storage efficiency of the ceramic is greatly improved.

[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lithium potassium tantalate niobate bismuth energy storage ceramic, characterized in that: Its chemical composition formula is (K 1-x Li x )[(Ta 0.63 Nb 0.37 ) 1-x Bi x ]O3, where 0<x≤0.

01.

2. The potassium lithium tantalate niobate bismuth energy storage ceramic according to claim 1, characterized in that: wherein 0.001≤x≤0.01, optionally 0.003≤x≤0.01, optionally 0.003≤x≤0.009, optionally 0.003≤x≤0.007, optionally 0.003≤x≤0.005; And / or, it is obtained by adding bismuth and lithium elements into a potassium tantalate niobate matrix.

3. The method for preparing the potassium lithium tantalate niobate bismuth energy storage ceramic according to claim 1 or 2, characterized in that: The steps include: Press (K 1-x Li x )[(Ta 0.63 Nb 0.37 ) 1-x Bi x ]The powders of K2CO3, Li2CO3, Nb2O5, Bi2O3 and Ta2O5 are mixed according to the molar ratio of K2CO3, Li2CO3, Nb2O5, Bi2O3 and Ta2O5, and the mixture is ball-milled for the first time, pre-fired, ball-milled again, granulated, formed, debinded and sintered to obtain potassium lithium tantalate niobate bismuth energy storage ceramics.

4. The preparation method according to claim 3, characterized in that: The first ball milling and / or the second ball milling are all wet ball milling; optionally, a volatile solvent is used as the medium for ball milling, and the volatile solvent is anhydrous ethanol. The ball milling time can be 21 to 24 hours; and zirconium oxide balls can be used for ball milling.

5. The preparation method according to claim 3 or 4, characterized in that: The pre-burning temperature is 750-800°C, and the pre-burning time is optionally 6-10 hours, and the atmosphere is optionally oxygen-free; the atmosphere is optionally air-free; the material after the first ball milling is heated to the pre-burning temperature at a rate of 1-5°C / min, and the rate of heating is optionally 2°C / min.

6. The preparation method according to any one of claims 3 to 5, characterized in that: Granulation includes: Adding a binder to the ball-milled material again for granulation; Optionally, the amount of binder added is 3-5wt%, optionally 4wt%; Optionally, the binder is polyvinyl alcohol; Optionally, before adding the binder, the ball-milled material is sieved through a 80-120 mesh sieve, optionally a 100 mesh sieve.

7. The preparation method according to any one of claims 3 to 6, characterized in that the forming include: The granulated particles obtained above are dry pressed at 100 MPa to obtain an embryo body; Optionally, the embryo body is a disc with a diameter of 10 mm and a thickness of 1.4 mm.

8. The preparation method according to any one of claims 3 to 7, characterized in that: Debinding includes heat preservation at 500-600°C, and the optional debinding heat preservation time is 80-120 minutes; Optionally, during the debinding process, the rate of heating to the insulation temperature is 1-5°C / min, and optionally 2°C / min.

9. The preparation method according to any one of claims 3 to 8, characterized in that: Sintering includes holding at 1170-1200°C; Optionally, the sintering holding time is 2-21 hours, optionally 10 to 21 hours, optionally 10 to 15 hours, optionally 12 to 15 hours; Optionally, during sintering, the rate of heating to the holding temperature is 0.5-5°C / min, and optionally 1-5°C / min.

10. Use of the potassium lithium tantalate niobate bismuth energy storage ceramic according to claim 1 or 2 or the potassium lithium tantalate niobate bismuth energy storage ceramic prepared by the preparation method according to any one of claims 3 to 9 in preparing capacitors.

Citation Information

Patent Citations

  • Erbium ytterbium-doped potassium lithium tantalite niobate ceramic and preparation method thereof

    CN105601286A

  • Potassium-sodium niobate based piezoelectric single crystal and preparation method thereof

    CN106521627A

  • Potassium tantalate niobate ceramic and preparation method thereof

    CN116041061A

  • Lead-free piezoelectric ceramics, manufacturing method thereof and actuator comprising thereof

    KR1020170042171A

  • Potassium sodium bismuth niobate tantalate zirconate ferrite ceramics with non-stoichiometric nb5+ and preparation method therefor

    US20240067572A1